IL RUOLO DEI GIOVANI CATTOLICI NEL VIVERE I VALORI DELLA SACRA BIBBIA NELLA COSTRUZIONE DELL'ARMONIA RELIGIOSA NELLA ISOLA DI TIMOR-NTT-INDONESIA - Abatan, Yofince; Abatan, Kasmirus; Boymau, Yerliani (STIPAS Keuskupan Agung Kupang, 2024)
Young Catholics are the next generation of sources of the Catholic faith. One of these is the holy book. The young Catholics of the island of Timor-NTT-Indonesia are very active in ecclesial activities. However, in reality, there are still many who do not have adequate knowledge and understanding of the Deuteurocanonical scriptures. This research aims to examine young Catholics' understanding and implementation of the Deuterocanonical Scriptures on the island of Timor-NTT and its impact on religious harmony. The method used is a qualitative approach with in-depth interviews and observations. The data obtained were reduced and analyzed so that they met the objectives of the research. The research results obtained show that young people's understanding of the Holy Bible is still minimal, especially regarding the differences between Catholic and Protestant holy books. However, the awareness of the importance of reading and meditating on the Holy Bible as a guide to life is quite high. To increase religious harmony on this island, intense socialization regarding the values ​​of the Deuterocanonical Scriptures is necessary. In conclusion, the values ​​contained in the Deuterocanonical Scriptures have great potential to strengthen relations between religious communities if well understood and implemented.